Maternal factors affecting the birth outcome of newborn at BPKIHS. - Mandal,Alpana (2018)
ABSTRACT: Background and objectives: maternal factors are the first determinants of the birth outcome of the newborn, which are closely related to perinatal morbidity and mortality. Newborn's health is related to maternal health. Maternal good health determines the good outcome of newborn. Poor birth outcomes are because of poor maternal health, inadequate care during pregnancy, and inappropriate management of complications during pregnancy and delivery, poor hygiene during delivery and the first critical hours after birth, and lack of newborn care. Hence, the objective of this study was to assess the factors affecting the birth outcome of newborn at BPKIHS. Material and method: A descriptive cross-sectional study was conducted in the maternity wards of BPKIHS. A total of 200 mothers and their babies were included, who were purposively selected meeting the inclusion criteria. Semi-structured, self-developed Interview schedule was used to collect data . Data was analyzed by using SPSS 20 version. Binary logistic regression analysis was applied to access association between maternal factors and the birth outcome of newborn at BPKIHS. Result: Study findings indicates that majority of the respondents (5835%) were in the age group 20-25 years followed by the age group 26-30(27.5%). The birth outcomes were categorized as (low birth weight, pattern birth, low APGAR score , condition of newborn which includes (alive or not alive), need for resuscitation, admission in nursery /NICU). The incident of low birth weight (<2.5kg) and preterm birth were found to be 26.0% and 8.5% respectively. Maternal factors like gestational age at delivery, pre-pregnancy BMI, occupation, type of family, education level, place of residence, cooking fuel, availability of separate kitchen, intake of folic acid tablets, problems during pregnancy mode of delivery, duration of labour, chronic and co-morbid conditions were the factors affecting birth outcomes of newborn. Conclusion: Finally, after binary logistic regression pre-pregnancy BMI, gestational age at delivery, occupation, educational status, mode of delivery, duration of labour, intake of folic acids, duration of calcium intake , problem with present pregnancy, chronic and co-morbid conditions were found as the significant predictors affecting birth outcome of newborn. Keywords: Birth outcome, maternal factors, Low birth weight, preterm birth, APGAR score, Resucitation, Condition of newborns, BPKIHS